Analisis Hukum Syuf’Ah Dalam Mazhab - Mazhab Fikih - Haris Dermawan; Nawir Yuslem; Akhyar Zen (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Syuf'ah is a legal institution in transactions aimed at protecting joint owners from potential losses resulting from the transfer of rights to third parties. This article examines the views of Islamic jurisprudence schools regarding the subject, object, and conditions for implementing syuf'ah, and analyzes the similarities and differences in the opinions of scholars. This research uses a juridical-normative method through a literature review of hadith evidence and the opinions of jurists. The study results show that all schools of thought agree on the validity of syuf'ah based on authentic hadith. This similarity of opinion is evident in the basic requirements of syuf'ah, namely joint ownership, an undivided object, immediate demand, and payment at the same price. Differences of opinion arise in determining the subject and object of syuf'ah, particularly regarding the extension of rights to neighbors and the scope of property, which are influenced by differences in istinbath methods, particularly the use of qiyas. This study confirms that the differences between schools of thought are methodological and do not eliminate the main objective of syuf'ah as an instrument to maintain public welfare, legal certainty, and justice in joint ownership.